LOCAL LABOR MARKETS AND NATURAL RESOURCES: A SYNTHESIS OF THE LITERATURE. (1st February 2017) - Marchand, Joseph; Weber, Jeremy
Abstract: A primary way that natural resources affect a locality is through the demand for labor, with greater extraction requiring more workers. Shifts in labor demand can be measured through changes in employment and earnings, the main labor market outcomes, or through changes in the population and income, more generally. These changes may spillover into the nonresource economy, leading to greater overall effects or possibly crowd out; be spread unequally across the population, thereby altering the distribution of income and the poverty rate; or influence educational attainment, as people choose between additional schooling and work. In this review, the literature linking natural resources to local labor markets is synthesized by organizing existing studies according to their resource measurement and the outcomes that they consider. This synthesis provides an accessible guide to a literature that has boomed in recent years. It also identifies promising avenues for future research and lays a foundation to further generalize the evidence through an eventual meta‐analysis.